Judicial Policy in Indonesia and Efforts to Strengthen the Rule of Law with Justice - Muhammad Maghfur Agung; Eza Tri Yandy; Sarkowi (ELQONUN: HUKUM KETATANEGARAAN ISLAM, 2026)
Judicial legal policy in Indonesia is an integral part of the dynamics of the formation, implementation, and reform of the national judicial system, which is based on the principles of justice, legal certainty, and the public interest. This study aims to analyze the direction and trends of legal policy in the judicial sector, including its impact on the independence of judicial institutions, access to justice, and the integrity of law enforcement. Using a normative legal method and a historical-comparative approach, this study finds that judicial legal policy in Indonesia is often influenced by the configuration of state power, political dynamics, and socio-economic pressures. Post-reform judicial reforms have brought significant changes, such as the establishment of the Judicial Commission, an integrated information technology-based judicial system, and a push for a clean and transparent judiciary. However, serious challenges remain, including political intervention, judicial corruption, and disparities in access to justice in regional areas. Therefore, the future direction of judicial legal policy must prioritize strengthening the rule of law, protecting human rights, and ensuring the independence of judicial institutions free from the interests of those in power.